Lorong Waktu Budaya Minangkabau: Sinergi Budaya dan Pariwisata di Perkampungan Adat Nagari Sijunjung - Ade Irwandi; Ermayanti Ermayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the synergy of culture and tourism in the Nagari Sijunjung traditional village. This research is an ethnographic study with observational data collection techniques, in-depth interviews, and literature studies. The results of this study indicate that cultural values such as traditional bakaua, batobo kongsi, mambatai adat and cultural manifestations in the form of gadang houses, artefacts are commodified as images and attractions for the tourism industry. Traditional bakaua cultural activities and batobo kongsi are packaged in the form of festivals. Likewise, Rumah Gadang is used as a homestay for guests who come to visit. So that creates a dilemma, between exalting cultural values as a traditional Minangkabau life tradition and the concept of Traditional Villages which are living monuments that are increasingly being eroded by the new culture of the tourism industry. The conclusion of this study is that Minang Kabau adat in Nagari is still upheld in everyday life. Minang Kabau identity can still be seen in the village of Nagari. Along with the times, the tourism industry began to grow rapidly up to the village of Nagari and efforts emerged to modify the village as a heritage tourism sector. Keywords: Commodification, Cultural Tourism, Nagari Sijunjung Traditional Village.